Young Taiwanese People’s Ethnic Identity and Stance on Independence vs. Unification: Regulating Effects of China’s (Asian Journal of Social Science Studies, 2023)
The study examines the relationship between ethnic identity, the unification-independence stance, and China's favorable measures among young Taiwanese individuals. It finds that there is a negative relationship between ethnic identity and the unification-independence stance, meaning that those with a stronger Taiwanese identity are more likely to support independence. However, China's favorable measures have a positive relationship with the unification-independence stance, indicating that they can influence young Taiwanese individuals to be more supportive of unification. The study also reveals that China's favorable measures strengthen the positive influence of ethnic identity on the unification-independence stance. Overall, the findings highlight the complex and multifaceted nature of political stances among young Taiwanese individuals, which can be influenced by factors such as economic opportunities, cultural exchanges, and educational cooperation with China. The study suggests further research to explore these relationships in more depth and to consider individual differences and temporal changes. Additionally, it recommends studying the impact of cross-cultural exchanges and conducting comparative research in cross-national contexts to gain a broader understanding of young people's political attitudes.